Prior Exposure to Angiotensin II Receptor Blockers in Patients With Septic Shock to Individualize Mean Arterial Pressure Target? A Post Hoc Analysis of the Sepsis and Mean Arterial Pressure (SEPSISPAM) Trial*. Issue 4 (12th February 2021) - Demiselle, Julien; Seegers, Valérie; Lemerle, Marie; Meziani, Ferhat; Grelon, Fabien; Megarbane, Bruno; Anguel, Nadia; Mira, Jean-Paul; Dequin, Pierre-François; Gergaud, Soizic; Weiss, Nicolas; Legay, François; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Individualizing a target mean arterial pressure is challenging during the initial resuscitation of patients with septic shock. The Sepsis and Mean Arterial Pressure (SEPSISPAM) trial suggested that targeting high mean arterial pressure might reduce the occurrence of acute kidney injury among those included patients with a past history of chronic hypertension. We investigated whether the class of antihypertensive medications used before the ICU stay in chronic hypertensive patients was associated with the severity of acute kidney injury occurring after inclusion, according to mean arterial pressure target. DESIGN: Post hoc analysis of the SEPSISPAM trial. SETTING: The primary outcome was the occurrence of severe acute kidney injury during the ICU stay defined as kidney disease improving global outcome stage 2 or higher. Secondary outcomes were mortality at day 28 and mortality at day 90. PATIENTS: All patients with chronic hypertension included in SEPSISPAM with available antihypertensive medications data in the hospitalization report were included. MEASUREMENTS AND MAIN RESULTS: We analyzed 297 patients. Severe acute kidney injury occurred in 184 patients, without difference according to pre-ICU exposure to antihypertensive medications. Patients with pre-ICU exposure to angiotensin II receptor blockers had significantly less severe acute kidney injury in the high mean arterial pressure target group (adjusted odd ratio 0.24 with 95% CI [0.09–0.66]; p = 0.006). No statistically significant association was found after adjustment for pre-ICU exposure to antihypertensive medications and survival. CONCLUSIONS: Our results suggest that patients with septic shock and chronic hypertension treated with angiotensin II receptor blocker may benefit from a high mean arterial pressure target to reduce the risk of acute kidney injury occurrence.